Metode Maximum Power Point Tracking (MPPT) dan Boost Converter Menggunakan Fuzzy Logic Controller (FLC) pada Modul Surya - Teuku Murisal Asyadi; Ira Devi Sara; Suriadi Suriadi (Jurnal Rekayasa Elektrika, 2021)
Solar modules have current and voltage characteristics that are non-linear, so efforts must always be made to work at the maximum power point so that no energy is wasted. The characteristics of the solar module will change depending on the level of radiation and temperature which causes the output power of the solar module to fluctuate and become unstable. To reduce oscillations in the output power of the solar module, the Fuzzy Logic Control (FLC) method used using the boost converter. Several studies have been done to maximize the output power of solar panels, one of which is by using namely by using Maximum Power Point Tracking (MPPT). This study aims to obtain the maximum power point in a set of solar modules arranged in series and parallel through the performance of the FLC method. In tracking the maximum power point during normal operation, the fuzzy method works together with a boost converter. Fuzzy-based MPPT was tested on a solar module under several radiation and temperature conditions using Matlab / Simulink software. The Fuzzy design method shows better results compared to other methods. The results obtained show the advantages of the FLC method in terms settling time, power loss, and oscillation at the point of the operating system.